2014
DOI: 10.3109/13561820.2014.917613
|View full text |Cite
|
Sign up to set email alerts
|

Student evaluations of an interprofessional education experience in pain management

Abstract: Interprofessional education (IPE) is vital to healthcare professionals and is especially relevant in the context of pain management. Despite its importance, it is often difficult to provide given limited time and resources and challenges with coordinating schedules across professions. This study explored satisfaction with a one-day IPE workshop on pain management. Seventy-three students from seven professions completed a questionnaire evaluating the workshop. Results suggested that students rated all aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“… 24 Studies of IPE have found differences between professions, with students in professions deemed psychosocial were more positive about IPE than students in biomedical career tracks. 13 Similarly, Erickson et al 9 found that IP mentorship and group participation improved first year medical students' pain management skills but did not have the same effect on fourth year nursing student performance. Differences were attributed in part to experience in clinical settings but also suggested that combining different levels of students is acceptable if they are of similar age and life experience.…”
Section: Outcomes Of Interprofessional Educationmentioning
confidence: 99%
“… 24 Studies of IPE have found differences between professions, with students in professions deemed psychosocial were more positive about IPE than students in biomedical career tracks. 13 Similarly, Erickson et al 9 found that IP mentorship and group participation improved first year medical students' pain management skills but did not have the same effect on fourth year nursing student performance. Differences were attributed in part to experience in clinical settings but also suggested that combining different levels of students is acceptable if they are of similar age and life experience.…”
Section: Outcomes Of Interprofessional Educationmentioning
confidence: 99%
“…This education would ideally overlap between different professional groups, both in academic and clinical environments, to ensure that HCP advice does not further disable or distress the person with LBP. Interprofessional education (IPE) is increasingly proposed as a means of preparing HCPs to collaboratively provide patient-centred clinical care for patients with pain [59,60], with some preliminary evidence demonstrating positive outcomes from pain-focussed IPE [61][62][63][64].…”
Section: Enhancing Lbp Beliefs Among Healthcare Students and Professimentioning
confidence: 99%
“…IPL has been shown to be effective for improving medical students’ pain competencies in a variety of settings, including general, paediatric and acute pain management [ 54 , 76 78 ]. However, medical schools in this study did not identify IPL as a delivery strategy for pain medicine education.…”
Section: Discussionmentioning
confidence: 99%